Pajak Bumi Dan Bangunan (PBB) - Fatimah Nainggolan; Nurcholiza Adha (CV. ITTC INDONESIA, 2026)
This study aims toi examine the influence iof taxpayers’ knowledge iand awareness on their complianci in paying Landiand Building Taxi (PBB), which serves as an importantisource of revenueifor supporting both national and regionalidevelopment. Following ithe implementationiof fiscalidecentralization through iLaw No. 28 of 2009, the management of iPBB for urban iand rural isectors (PBB-P2) has beenidelegated to localigovernments, making it a significant componentiof Regional Original Incomei (PAD). This article reviewsithe definition, ilegal basis, objectives, and collectionimechanisms of PBB, along with the challenges and efforti to improve itsisystem. Despite its strategic importance, theiimplementation ofiPBB stillifaces obstaclesisuch as low taxpayer compliance, inaccurate determination of the Sales Value of Taxable Objects (NJOP), andiweak administrativeisystems. Therefore, iinnovations including service digitalization, continuous data updating, and enhanced public education are necessary to optimize PBB as a fair and sustainabli fiscal instrument.